2021
DOI: 10.1177/02692163211017387
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and addressing challenges for advance care planning in the COVID-19 pandemic: An analysis of the UK CovPall survey data from specialist palliative care services

Abstract: Background: Specialist palliative care services play an important role in conducting advance care planning during COVID-19. Little is known about the challenges to advance care planning in this context, or the changes services made to adapt. Aim: Describe the challenges that UK specialist palliative care services experienced regarding advance care planning during COVID-19 and changes made to support timely conversations. Design: Online survey of UK palliative/hospice services’ response to COVID-19. Closed-ende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 50 publications
(73 reference statements)
0
56
0
2
Order By: Relevance
“…Third, advance care planning and decision-making were further challenged by both the lack of knowledge, and the huge amount of uncertainty, regarding the clinical course and prognosis of COVID-19 as well as time constraints. Because of these time constraints, clinicians found they had to rush their advance care planning conversations [ 20 ]. Healthcare providers observed that media coverage increased fear among patients and families that clinical decisions were made in the context of limited resources [ 20 ].…”
Section: Palliative Care Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, advance care planning and decision-making were further challenged by both the lack of knowledge, and the huge amount of uncertainty, regarding the clinical course and prognosis of COVID-19 as well as time constraints. Because of these time constraints, clinicians found they had to rush their advance care planning conversations [ 20 ]. Healthcare providers observed that media coverage increased fear among patients and families that clinical decisions were made in the context of limited resources [ 20 ].…”
Section: Palliative Care Challengesmentioning
confidence: 99%
“…Because of these time constraints, clinicians found they had to rush their advance care planning conversations [ 20 ]. Healthcare providers observed that media coverage increased fear among patients and families that clinical decisions were made in the context of limited resources [ 20 ].…”
Section: Palliative Care Challengesmentioning
confidence: 99%
“…A combination of dealing with death and dying, risks of infection, personal loss/grief, and operating in insufficiently resourced services has resulted in many experiencing anxiety, depression, insomnia, burnout, and post-traumatic stress disorder. [4][5][6][7][8] Palliative care is a unique speciality in that staff are used to dealing with dying and may have been less affected by this aspect of the COVID-19 pandemic. Nevertheless, in responding to COVID-19, palliative care professionals have been confronted with constraints and obstacles (e.g., making complex and difficult decisions, infection control, dealing with uncertainty, and recognising deep inequities 6,9,10 ) that have severely challenged their ability to provide care in accordance with their professional values.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Palliative care is a unique speciality in that staff are used to dealing with dying and may have been less affected by this aspect of the COVID-19 pandemic. Nevertheless, in responding to COVID-19, palliative care professionals have been confronted with constraints and obstacles (e.g., making complex and difficult decisions, infection control, dealing with uncertainty, and recognising deep inequities 6,9,10 ) that have severely challenged their ability to provide care in accordance with their professional values. These values include alleviating suffering and enhancing the quality of life of dying patients and their families through the adoption of a holistic, compassionate, person-centred, dignified, safe, and multidisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, two papers help address the timing and urgency questions which arose during the COVID-19 pandemic. Bradshaw et al 8 from the CovPall study 9,10 report on changes that UK specialist palliative care services made to support timely conversations, and the challenges they experienced in advance care planning. Lack of face-toface contact resulted in loss of key communication strategies, impacting on the ability to develop rapport with individuals, through identifying and responding to nonverbal cues, particularly where capacity, cultural or language issues were also present.…”
mentioning
confidence: 99%